Multicomponent syntheses of 5- and 6-membered aromatic heterocycles using group 4–8 transition metal catalysts. Issue 28 (6th July 2021) - Huh, Daniel N.; Cheng, Yukun; Frye, Connor W.; Egger, Dominic T.; Tonks, Ian A.
Abstract : In this Perspective, we discuss recent syntheses of 5- and 6-membered aromatic heterocycles via multicomponent reactions (MCRs) catalyzed by group 4–8 transition metals, with a focus on common mechanisms and synthetic strategies across the series. Abstract : In this Perspective, we discuss recent syntheses of 5- and 6-membered aromatic heterocycles via multicomponent reactions (MCRs) that are catalyzed by group 4–8 transition metals. These MCRs can be categorized based on the substrate components used to generate the cyclized product, as well as on common mechanistic features between the catalyst systems. These particular groupings are intended to highlight mechanistic and strategic similarities between otherwise disparate transition metals and to encourage future work exploring related systems with otherwise-overlooked elements. Importantly, in many cases these early- to mid-transition metal catalysts have been shown to be as effective for heterocycle syntheses as the later (and more commonly implemented) group 9–11 metals.